A new sesquiterpenoid quinone with cytotoxicity from Abelmoschus sagittifolius. Issue 5 (3rd March 2016) - Chen, De-Li; Zhang, Xiao-Po; Ma, Guo-Xu; Wu, Hai-Feng; Yang, Jun-Shan; Xu, Xu-Dong
Abstract : A new sesquiterpenoid quinone, Acyl hibiscone B (1 ), together with five known compounds, ( R )-lasiodiplodin (2 ), ( R )-de- O -methyllasiodiplodin, (3 ) dibutyl phthalate (4 ), ( R )-9-phenylnonan-2-ol (5 ) and hibiscone B (6 ), was obtained from the stem tuber of Abelmoschus sagittifolius . The structure of compound1 was elucidated by analysing its 1 H and 13 C NMR, 1 H– 1 H COSY, HSQC, HMBC, NOESY and HR-ESI-MS values. Compound1 showed significant cytotoxicity against Hela and HepG-2 human cancer cell lines. Abstract :